MENINGKATKAN PROFESIONALITAS GURU DI ERA MASYARAKAT EKONOMI ASEAN (MEA)DI YAYASAN PERGURUAN ALMA’SHUM SIDODADI KABUPATEN ASAHAN - Uswatun Hasanah; Zulfi Azhar (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2018)
Abstract: The challenges in the world of education today, especially in the Era of the Asean Economic Community (MEA) is quite heavy, where the world of education must be able to adjust to the current conditions. Starting from policy makers who have to think about breakthroughs in the form of rules up to the educational implementer who can immediately act to improve the learning process to fit the need for market share in this era of competition. Participants Community service activities conducted at the Alma'shum Perguruan Foundation Sidodadi Village District West Kisaran is the teachers who teach at the Foundation of Alma'shum College. The purpose of this activity Provide information and knowledge about the role of teachers in the era of ASEAN Economic Community and Provide Information and knowledge about the importance of technology mastery in facing global challenges. The team of lecturers who conduct this activity consists of lecturers who have different educational background. The result of this activity is the approval of the follow up activities to improve the competence of lecturers especially in the field of Information Technology.Keywords: Profesionalism MEA, Competence, Teacher, TIAbstrak: Tantangan  dalam dunia pendidikan saat ini terutama di Era Masyarakat Ekonomi Asean (MEA)  cukup berat, dimana dunia pendidikan harus mampu menyesuaikan dengan  kondisi saat ini. Mulai dari pembuat kebijakan yang harus memikirkan terobosan dalam bentuk aturan sampai dengan pelaksana pendidikan yang dengan segera bisa bertindak untuk memperbaiki proses pembelajaran agar sesuai dengan kebutuhan akan pangsa pasar di era persaingan seperti ini. Peserta Kegiatan pengabdian masyarakat yang dilakukan di  Yayasan Perguruan Alma’shum Kelurahan Sidodadi Kecamatan Kisaran Barat ini adalah guru-guru yang mengajar di Yayasan Perguruan Alma’shum. Tujuan dari kegiatan ini   Memberikan informasi dan pengetahuan tentang peranan guru dalam era Masyarakat Ekonomi Asean dan Memberikan Informasi dan pengetahuan tentang pentingnya penguasaan teknologi  dalam menghadapi tantangan global. Tim dosen yang melakukan  kegiatan ini terdiri dari dosen-dosen yang memiliki latar pendidikan yang berbeda. Hasil dari kegiatan ini adalah disepakatinya kegiatan lanjutan  guna meningkatkan  kompetensi dosen terutama di bidang Teknologi InformasiKata kunci: Profesionalitas, MEA, Kompetensi, Guru, TI